Looking for more food or more people? Task context influences basic numerosity perception. (May 2019) - Fornaciai, Michele; Farrell, Abigail; Park, Joonkoo
Abstract: Approximate numerical magnitude (or numerosity) is thought to represent one of the fundamental sensory properties driving perceptual choices. Recent studies indicate that numerosity judgment on a dot array is primarily driven by its numerical magnitude, largely independent from its other non-numerical visual dimensions. Nevertheless, these findings do not preclude the possibility that non-numerical cues such as size or spacing of a dot array influence numerosity judgment. Here, we test the hypothesis that numerosity judgment is influenced by non-numerical dimensions of a dot array depending on the context to which those non-numerical cues could be useful. Participants were asked to choose the more numerous of two dot arrays in two different contexts that differed only in one aspect. In one condition, the task was framed as choosing a set with more fruits to consume. In the other condition, the task was framed as choosing a group with more people to join. The results demonstrate that the influence of non-numerical cues – and particularly of the dimension of size – was significantly smaller when participants made quantitative choices about people than when they made choices about food, illustrating that the representation of discrete magnitude is more pronounced in the former case. These findings suggest that the information pooled to reach a decision about numerosity is flexibly determined according to the context and the goals of such judgment.